2020
DOI: 10.1001/jamaoncol.2019.2974
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Successful Discontinuation of Immune Suppression After Allogeneic Hematopoietic Cell Transplantation

Abstract: IMPORTANCE Immune suppression discontinuation is routinely attempted after allogeneic hematopoietic cell transplantation (HCT) and under current practices may lead to graft-vs-host disease (GVHD)-associated morbidity and death. However, the likelihood and predictive factors associated with successful immune suppression discontinuation after HCT are poorly understood.OBJECTIVES To examine factors associated with successful immune suppression discontinuation and risk for immune suppression discontinuation failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Chronic graft vs. host disease (GVHD) is a common complication of allogeneic hematopoietic cell transplantation (HCT), 1 and is associated with increased risk of death, morbidity, impaired quality of life, and prolonged immune suppressive (IS) therapy. [2][3][4][5][6][7] Based on evidence arising from prior clinical trials as well as practice recommendations, initial therapy for chronic GVHD remains prednisone (generally starting at 1mg/kg/day) with or without a calcineurin inhibitor. Previous work has demonstrated that this approach fails to provide durable control of chronic GVHD, as failure-free survival (a composite failure endpoint including death, malignancy relapse, or additional systemic IS therapy) following initial steroid therapy is 68% by 6 months, and 54% by 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic graft vs. host disease (GVHD) is a common complication of allogeneic hematopoietic cell transplantation (HCT), 1 and is associated with increased risk of death, morbidity, impaired quality of life, and prolonged immune suppressive (IS) therapy. [2][3][4][5][6][7] Based on evidence arising from prior clinical trials as well as practice recommendations, initial therapy for chronic GVHD remains prednisone (generally starting at 1mg/kg/day) with or without a calcineurin inhibitor. Previous work has demonstrated that this approach fails to provide durable control of chronic GVHD, as failure-free survival (a composite failure endpoint including death, malignancy relapse, or additional systemic IS therapy) following initial steroid therapy is 68% by 6 months, and 54% by 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional calcineurin-based regimens, it is uncommon to discontinue IS (20%) and relatively common for other IS forms (including steroids) to be used for long periods after transplantation. Additionally, in newer strategies, the burden of IS persists— albeit significantly less pronounced [ 25 , 33 , 46 , 47 ]. After PTCy-BMT, the cumulative incidence of steroid use at three years ranges between 46& and 68%; the probability of being alive and free from IS ranges between 48–56%, with 10–20% of patients conditioned with busulfan/fludarabine still on IS at 3 years [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis examined successful discontinuation of IST and incidence of GVHD recurrence in 827 patients enrolled in two phase III clinical trials using CNI-based GVHD prophylaxis. 124 Only 20% of patients were alive and off IST completely at 5 years. A total of 41.4% of patients were able to discontinue IST initially; however, 37.1% had discontinuation failure and had to restart IST for GVHD.…”
Section: Clinical Implications Of Cgvhd Managementmentioning
confidence: 98%